L–Arginine and l–Lysine improve the physical stability of soybean oil–myosin emulsions by changing penetration and unfolding behaviors of interfacial myosin. (January 2020) - Li, Linxian; Chen, Li; Ning, Cheng; Bao, Pengqi; Fang, Hongmei; Zhou, Cunliu
Abstract: This study investigated the mechanisms underlying the influence ofl –Arginine (Arg)/l –Lysine (Lys) on the physical stability of soybean oil–myosin emulsions (SOME). Results indicated that Arg and Lys increased emulsifying activity index and emulsifying stability index, but decreased the residual protein content in the aqueous phase, CI and oil droplet size of SOME. Arg increased the interfacial pressure (π) of SOME and increased the penetration rate (kP ) but decreased the diffusion rate (kdiff ) of interfacial myosin. Lys increased the kP but decreased the kdiff of the interfacial myosin and decreased the π of SOME. Lys reduced the rearrangement rate of interfacial myosin; Arg only slightly affected it. Lys was more effective than Arg in exposing tyrosine and tryptophan residues of interfacial myosin; Arg was more conducive than Lys for structurally transforming interfacial myosin from disordered to ordered. These results confirm that Arg and Lys changed the structure and penetration of interfacial myosin, improving the physical stability of SOME. Graphical abstract: Image 1 Highlights: Arginine/Lysine increased the physical stability of soybean oil–myosin emulsion Arginine increased the pressure of soybean oil–water interface, whereas lysine decreased it Arginine/Lysine slowed down the diffusion but fastened the penetration of myosin Lysine retarded the rearrangement of myosin, and arginine only slightly affected it Arginine/Lysine caused a blue shift at 274 nm and higher α–helices and β–sheets